Vietnam : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This Selected Issues paper for Vietnam reports that the framework for policy lending in Vietnam, in conjunction with the active consideration of proposals to enhance the operational autonomy of policy-lending institutions, poses significant risks. The current framework does not adequately address common governance issues related to state involvement in investment decisions, and is insufficient to ensure the quality of investment. Recommended policy actions include removing residual policy lending from commercial banks, and improving prudential regulations and supervision of the Development Assistance Fund and local development funds well before they are granted any significant autonomy.